Reconciliation Processes in Iraq. The Potential ofTruth Commissions on Bringing Democracy - Garcia, Ana (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. After many years of civil war and conflicts, Iraq is still currently involved in increased levels of sectarian violence. The American intervention in Iraq in 2003 and the more recent withdrawal of the international troops from the country have directly contributed to the crescent instability in the country. Achieving reconciliation within and between the different sectarian groups living in Iraq is missing. The implementation of a reconciliation process can bring not only knowledge and understanding about past crimes and violations of human rights committed, but also it can help building a new institutional democratic structure. In this regard, truth commissions on a national level have proven to be effective reconciliation instruments in contexts of grave violation of human rights, such as Iraq. Approaching a past history of violation of human rights with both the government and communities directly affected can have the potential to establish the bases for a long-term democratic system.